Existe efeito do cinturão digital na qualidade do acesso à internet nas escolas públicas estaduais do Ceará ? uma análise sobre a percepção dos diretores - Pereira, Francisco Sérgio Rodrigues (2014)
Digital Belt design of Ceará (CDC) is an initiative of the local government, in partnership with the Ministry of science, technology and innovation (MCTI), to provide high-speed internet, with quality, aiming to universalize the access to information. This work aims to analyze whether there is Digital belt effect on the quality of internet access in public schools State of Ceará. This measure of quality is defined by perceptions of Directors, drawn from socio-economic questionnaires contained in Brazil (INEP) relating to periods of 2009 (before the project), and 2011 (after implementation of the CDC). As not all schools were benefited by the CDC, it has been possible to employ the method of differences in differences, to assess the results and impacts caused by the project. It was found by descriptive statistics that the directors of the schools benefited realized an improvement absolute and relative quality of internet access for use of the student use. The differential in favour of these was 7.4 percentage points in the medium. In estimated logit model, however, the positive differential in favour of schools benefited was not statistically significant, causing the impact results are not robust.